Dialing it in: A Missed Opportunity Regarding the Strategic Use of Telework? - Cooke, Gordon; Chowhan, James; Cooper, Tom (Relations industrielles / Industrial Relations, 2014)
SummaryThe purpose of this paper is to examine the degree of alignment of organizational strategies with two types of telework using Statistics Canada’s 2005 Workplace and Employee Survey data. In this paper, we intentionally use the most inclusive definition of telework, because we are interested in all cases where an employee works from home at least some of the time. We consider telework to be ‘employee-oriented’ when an employee works at home to address his and her family-related or personal wants or needs, and ‘employer-oriented’ when an employee works at home due to the employer’s strategic or operational objectives. The three organizational strategies that we considered were innovation, involvement, and cost-containment. We found that employers focusing on innovation were significantly more likely than other employers to use both types of telework, with greater emphasis on employee-oriented telework, whereas employers using an involvement strategy were less likely to use either type of telework, albeit at only a weak level of significance. Moreover, we did not find a statistical relationship between the cost containment strategy and either type of telework. We hypothesized that employee-oriented telework would be more common among workers in workplaces focusing on innovation or involvement, but less common among workers in workplaces focusing on cost containment. We hypothesized the reverse situation for the incidence of employer-oriented telework. On the whole, the results suggested that employers are not universally aligning the implementation of the two types of telework with their organizational strategies. Rather, either telework is not commonly used as a strategic tool or, alternatively, the strategic implementation of these two types of telework is more contingent upon other organizational or employee factors in specific circumstances.